1998
DOI: 10.1121/1.423249
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and period discrimination of haptic stimuli

Abstract: As part of a project to examine the ability of the hand to receive speech information, the present study examined subjects' ability to discriminate finger movements along the dimensions of amplitude and period (movement duration). The movements consisted of single-cycle, sinewave movements and single-cycle, cosine movements presented to the index finger. Difference thresholds were collected using an adaptive, two-interval, temporal forced-choice procedure. Amplitudes from 6 to 19 mm were examined, and the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Although many studies determined passive frequency JNDs, the authors are not aware of any data on active frequency JNDs that are required for the design of an improved shared controller. Rinker et al [17] investigated frequency JND in pseudo-active movements of the finger and the JNDs were similar to those obtained passively in [7]. In the present study, a human's ability to discriminate natural frequency of virtual dynamic systems is investigated by asking participants to actively excite the system while coupled with a handle of a single degree-of-freedom haptic device 1 .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although many studies determined passive frequency JNDs, the authors are not aware of any data on active frequency JNDs that are required for the design of an improved shared controller. Rinker et al [17] investigated frequency JND in pseudo-active movements of the finger and the JNDs were similar to those obtained passively in [7]. In the present study, a human's ability to discriminate natural frequency of virtual dynamic systems is investigated by asking participants to actively excite the system while coupled with a handle of a single degree-of-freedom haptic device 1 .…”
Section: Introductionmentioning
confidence: 54%
“…Active perception of natural frequency required the participant to excite the system through their own movement of the haptic interface handle. Previous studies have determined frequency and period discrimination thresholds (or Weber fractions) for low-frequency sinusoidal waveforms by moving participants' fingerpads loosely placed on a contactor [7,17]. However, a human's ability to discriminate frequency of a manually excited dynamic system has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have determined the frequency and period discrimination thresholds (or WF) for low-frequency sinusoidal waveforms on passive fingerpads [20], [24]. However, a human's ability to discriminate the natural frequency of a manually excited dynamic system has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the same reference natural frequency is rendered with two distinct physical parameter sets, resulting in distinct interaction force profiles. In [24], Rinker et al suggest that participants might be using the so called intensity perception as a basis of frequency discrimination. Similarly, in [15], Tan et al showed that their participants used force and work cues in compliance (inverse of stiffness) discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have documented tactile frequency and amplitude resolution (cf. [4]), few have addressed the effects of background maskers on resolution ability (although see [5]). The present set of experiments provided a systematic measurement of frequency and amplitude discrimination thresholds for sinusoidal displacement waveforms delivered to a fingertip with or without the presence of other masking background signals.…”
Section: Introductionmentioning
confidence: 99%